Next-Generation Sequencing Revealed Disease-Causing Variants in Two Genes in a Patient With Combined Features of Spherocytosis and Antley-Bixler Syndrome With Genital Anomalies and Disordered Steroidogenesis - Song, Fuying; Feng, Shunqiao; Shen, Xiang; Du, Mu; Yin, Hui; Liu, Rong; Chen, Xiaobo (Frontiers in Genetics, 2020)
Conventionally, patients with combined rare diseases are often hard to diagnosed by the diagnostic routine. This is because in the common thinking model, the multiple disease symptoms are tending to be considered as the presentation of a complicated “syndrome”. This thinking pattern also confine their way of filtering pathogenic mutations. The real pathogenic mutations might be ignored due to not covering all disease presentations. Here we report a case of a girl who was suffered from spherocytosis and antley-bixler syndrome with genital anomalies and disordered steroidogenesis. She remained undiagnosed even after gene detection before. However, after doing the Next-generation sequencing and the analysis of the sequencing data, we identified two mutations, c.2978T>A in ANK1 and mutation c.1370G>A in POR gene. Our findings and experience in the diagnosis could expand the thoughts in clinical and genetic diagnosis of patients with multiple systems involved.